Perceptions of Child Abuse as Manifested in Drawings and Narratives by Children and Adolescents - Goldner, Limor; Lev-Wiesel, Rachel; Binson, Bussakorn (Frontiers in Psychology, 2021)
Child abuse is an underreported phenomenon despite its high global prevalence. This study investigated how child abuse is perceived by children and adolescents as manifested in their drawings and narratives, based on the well-established notion that drawings serve as a window into children's mental states. A sample of 97 Israeli children and adolescents aged 6 to 17 were asked to draw and narrate what child abuse meant to them. The drawings and narratives were coded quantitatively. The results indicated that participants did not perceive a distinction between abuse and violence and referred to them interchangeably. Almost half of the participants focused on emotional abuse. The most frequent type of abuse within the family was between parents and children, and the most frequent abuse outside the family was peer victimization. Most of the drawings were figurative and realistic and half of the drawings included words suggestive of the participants’ attempts to be heard and fully understood. The vast majority of drawings did not include the figure of the artist, about a third of the drawings employed dissociative techniques (i.e., included positive objects, were unrelated to abuse, used words alone, or did not follow the instructions), and almost half of the narratives were dissociative or characterized by negative resolution, describing feelings such as sadness, humiliation, and loneliness. These findings suggest the emotional pain associated with the abuse or violence and the use of dissociative mechanisms to bypass the pain. The findings are discussed in light of the literature on children’s disclosure.